Populasi Monyet Ekor Panjang (Macaca fascicularis) di TWA Grojogan Sewu, Tawangmangu, Karanganyar, Jawa Tengah - Tri Satyatama (Indonesian Journal of Conservation, 2023)
Long-tailed monkeys (Macaca fascicularis) in TWA Grojogan Sewu, Karanganyar, Central Java, apart from being an attraction, also cause problems in the form of disturbance to visitors and traders in the tourist area. In order to control the long-tailed monkey population in this conservation area, it is necessary to carry out a survey aimed at calculating the population of these animals in and around the Grojogan Sewu TWA area, using the concentration count method. The survey results showed that the population of long-tailed monkeys in TWA Grojogan Sewu was 128 individuals, consisting of 4 groups with the number of individuals per group ranging from 17 to 44 individuals.